Aerodynamic Analysis on Noise Generated from Automotive Side Mirror Using CFD - Sapit, Azwan; Jamaludin, Nik Muhammad Jafni (Progress in Aerospace and Aviation Technology, 2022)
The geometry of the car side mirror influences the aerodynamic noise. In this research will investigates aerodynamic analysis on noise from the side mirror using Computational fluid dynamic CFD. In study will design side mirror 2 type of design Honda Civic EG9 category sedan and Range Rover Evoque category SUV. Additionally, one of the goals of this study is to evaluate the model’s CFD simulation the design built using the SolidWorks software, and the simulation run using the ANSYS software. The methodology research was by simulating the side mirror models with three velocity values (80 km/h,100km/h, 120 km/h). The analysis of the side mirror’s drag force, acoustic contour, and velocity streamlines will determine the results that must be compared. Design 1, a sedan, produces a maximum acoustic power level of 77.21 dB when travelling at a high speed of 120 km/h. The maximum acoustic power level for Design 2 SUV cars travelling at 120 km/h is 75.71dB. In summary, design 2’s side mirror has a higher acoustic power level than design 1’s side mirror. the force that opposes the motion of a body that is filled with fluid. Design 1, a sedan, produces a drag force of 4.52 N at a high speed of 120 km/h. Design 2, an SUV, results in a drag force of 6.36 N at a high speed of 120 km/h. Lastly, this research benefits car manufacturing companies by changing design side mirror the can decrease cabin noise. This will improve ride quality, especially since electric vehicles dominate the market with no engine noise.